Biohacking, Bodies and Do-It-Yourself The Cultural Politics of Hacking Life Itself - Grewe-Salfeld, Mirjam (American Culture Studies, 2021)
From self-help books and nootropics, to self-tracking and home health tests, to the tinkering with technology and biological particles - biohacking brings biology, medicine, and the material foundation of life into the sphere of »do-it-yourself«. This trend has the potential to fundamentally change people's relationship with their bodies and biology but it also creates new cultural narratives of responsibility, authority, and differentiation. Covering a broad range of examples, this book explores practices and representations of biohacking in popular culture, discussing their ambiguous position between empowerment and requirement, promise and prescription.